2019
DOI: 10.1111/jdv.16102
|View full text |Cite
|
Sign up to set email alerts
|

GLUT1 expression in human papillomavirus‐positive anogenital lesions

Abstract: Background GLUT1, an ubiquitous glucose transporter in the mammalian cells, is upregulated in many tumours, including human papillomavirus (HPV)‐induced head and neck or cervical cancer. Objective To study in anogenital lesions whether or not GLUT1 expression correlates with genomic high‐risk HPV integration, the first step in neoplastic transformation. Methods Forty‐three HPV‐positive biopsies positive for either low‐risk or high‐risk HPV were selected. Paraffin sections adjacent to those tested for the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Higher expression of GLUT1 is an independent prognostic factor for the overall survival of HPV16-positive patients, and HPV16-positive patients overexpressing GLUT1 have lower immune cell scores of CD8+ T cells, B cells and Th1 cells [67]. GLUT1 expression correlates with HPV infection [68]. Several pathways may contribute to the regulation of GLUT1 in cervical cancer.…”
Section: Metabolic Features In Cervical Cancer and Carcinogenesis Eff...mentioning
confidence: 99%
“…Higher expression of GLUT1 is an independent prognostic factor for the overall survival of HPV16-positive patients, and HPV16-positive patients overexpressing GLUT1 have lower immune cell scores of CD8+ T cells, B cells and Th1 cells [67]. GLUT1 expression correlates with HPV infection [68]. Several pathways may contribute to the regulation of GLUT1 in cervical cancer.…”
Section: Metabolic Features In Cervical Cancer and Carcinogenesis Eff...mentioning
confidence: 99%
“…Recently, digital staining was introduced within the imaging process, which mimics conventional H&E histopathology successfully. 1 Correlations between CLSM imaging and classic histopathology have been studied in detail for healthy human skin and non-melanoma skin cancer with promising results [2][3][4][5][6] ; only one study has evaluated inflammatory diseases. 7 Cutaneous inflammatory diseases can be complex to distinguish clinically and histologically.…”
Section: Doi: 101111/jdv16992mentioning
confidence: 99%
“…Kariya et al 1 reported that keratinocytes in PET-positive seborrhoeic keratosis showed higher glucose transporter (GLUT) 1 and GLUT3 expressions than those observed in PET-negative seborrhoeic keratosis and normal skin. Samama et al 5 reported a correlation between GLUT1 overexpression and the number of episomally HPV infected cells in the skin. Therefore, aberrant GLUT expression may enhance FDG uptake in such lesions.…”
mentioning
confidence: 99%